2020
DOI: 10.1093/jge/gxaa021
|View full text |Cite
|
Sign up to set email alerts
|

Extension of grouting-induced splitting fractures in materials similar to coal rocks containing prefabricated fractures

Abstract: To reveal the influence of prefabricated fractures (PFs) with different parameters on the extension of grouting-induced splitting fractures, a combination of numerical simulation and physical experiments were used to carry out grouting trials on similar materials to coal rock. The RFPA software was used to simulate the whole process of fracture initiation and expansion of coal rock with PFs during grouting. In the experiment, acoustic emission (AE) technology was used to monitor the extension process of grouti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The derivation above describes the grouting process of the slurry in the flow core area of the Bingham fluid in the crack. The grouting process is determined by the rheology of the slurry, geometric parameters of the crack, operating parameters, and the groundwater environment . These parameters control the grouting pressure, pressure distribution in the grouting area, and diffusion length of the injected slurry in the plane crack.…”
Section: Diffusion Analysis Model Of Bingham Flow Pattern Slurry In P...mentioning
confidence: 99%
“…The derivation above describes the grouting process of the slurry in the flow core area of the Bingham fluid in the crack. The grouting process is determined by the rheology of the slurry, geometric parameters of the crack, operating parameters, and the groundwater environment . These parameters control the grouting pressure, pressure distribution in the grouting area, and diffusion length of the injected slurry in the plane crack.…”
Section: Diffusion Analysis Model Of Bingham Flow Pattern Slurry In P...mentioning
confidence: 99%
“…Based on the rapid development of computer, some scholars used finite element method, finite difference method and discrete element method to build the rock mass grouting model, analyzed the changes of grout velocity field, displacement field and stress field, and further improved the development of grout diffusion filling law. But most of the studies were based on single fissure or orthogonal fissure rock mass [11][12][13]. There is a certain gap between it and the actual fractured rock mass.…”
Section: Introductionmentioning
confidence: 99%
“…Warpinski and Teufel et al (1987) revealed from field results that the in-situ stress and fluid pressure could influence the hydraulic fracturing procedure. The effects of elastic modulus, Poisson's ratio, and in-situ stress on fracture geometry were studied by means of experiment and field investigation (Liang et al, 2017;Chen et al, 2019;Hu et al, 2020;Liu et al, 2020). For instance, Li et al (2014) comprehensively studied the effect of the formation mechanical property (in-situ stress, elastic modulus, and permeability) differences between adjacent layers over hydraulic fracture propagation, and it turned out that the mechanical properties of strata have a great influence on the fracture extension; Yinlong investigated the influence of the intermediate principal stress on the mechanical properties of cubic coal and soft sandstone under two different true triaxial loading conditions and discussed the influence interval of the intermediate principal stress on the strength of sandstone and coal in detail.…”
Section: Introductionmentioning
confidence: 99%